2020
DOI: 10.3390/ijms21207495
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Albuminuria Reduction by Chymase Inhibition in Diabetic Mice

Abstract: Chymase has several functions, such as angiotensin II formation, which can promote diabetic kidney disease (DKD). In this study, we evaluated the effect of the chymase inhibitor TY-51469 on DKD in diabetic db/db mice. Diabetic mice were administered TY-51469 (10 mg/kg/day) or placebo for 4 weeks. No significant difference was observed in body weight and fasting blood glucose between TY-51469- and placebo-treated groups. However, a significant reduction in urinary albumin/creatinine ratio was observed in the TY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Podocyte damage is relieved in db/db mice when podocytes are treated with a chymase inhibitor. These results suggest that podocyte injury in the glomerulus is caused by a chymase-dependent AngII-generating system ( 28 ). Regarding the regulation of chymase activity, SERPINA3 can inhibit several serine proteases secreted from neutrophils and mast cells, including chymase ( 31 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Podocyte damage is relieved in db/db mice when podocytes are treated with a chymase inhibitor. These results suggest that podocyte injury in the glomerulus is caused by a chymase-dependent AngII-generating system ( 28 ). Regarding the regulation of chymase activity, SERPINA3 can inhibit several serine proteases secreted from neutrophils and mast cells, including chymase ( 31 ).…”
Section: Discussionmentioning
confidence: 95%
“…Chymase secreted by mast cells is involved in vasoactive peptide generation, extracellular matrix degradation, and glandular secretion regulation ( 28 , 29 ). Chymase is associated with diabetic renal tubular injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disodium cromoglycate could inhibit the degranulation of mast cells and lighten tubulointerstitial collagen deposition in rats with type I diabetes ( 34 ). Chymase inhibitor TY-51469 suppressed oxidative stress in the renal podocytes of diabetic db/db mice, thereby decreasing albuminuria ( 35 ). This evidence revealed that mast cells were involved in DN progression.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were pretreated with consecutive intraperitoneal doses of 10 mg/kg TY‐51469, 11 , 29 according to the following scheme: 48 hours, 24 hours, and 30 minutes before IVC ligation. Animals were euthanized 24 hours after ligation.…”
Section: Methodsmentioning
confidence: 99%